Workplace Incivility –Resident's Perspective - Uzma Ahsan , Lamia Yusuf , Maria Aslam , Aqsa Aslam , Ahsan Nasim , Muhammad Hashim Khan (Journal of Islamic International Medical College)
Objective: To explore postgraduate residents' perceptions of workplace incivility and its impact on their emotional status and job performance. Study Design: Qualitative phenomenon study. Place and Duration of Study: Sharif Medical & Dental College, Lahore from 1st February 2023 to 1 September 2023. Materials and Methods: Fourteen postgraduate residents were selected through purposive, qualitative sampling. In-depth interviews were audiotaped, and simultaneous field notes were taken. After the identification of any new theme after 14 participants, three more participants were interviewed till the data saturation point was achieved. Data verification was done through an audit by the researchers. The responses from these interviews were evaluated and themes were identified which were further explained in subthemes. The qualitative data was from audiotaped narratives, transcriptions, and field notes capturing participants' perceptions and experiences. Otter.ai was employed for the transcription of the recorded interviews, streamlining the process of converting audio data into text. Microsoft Word was used for further editing and organizing transcriptions. A word cloud generator, WordArt, was utilized for the graphical representation of themes and subthemes. Results: Five themes and nine subthemes were identified. The themes derived were types of workplace incivility, emotional impact of workplace incivility, impact on professional development, coping mechanisms and addressing & preventing workplace incivility. The subthemes were subtle microaggressions, verbal disrespect, emotional distress, undermined confidence, stifled growth, compromised patient care, seeking support, finding allies and reflecting & self-care. Conclusion: Our study determined that the most common types of workplace incivility among postgraduate trainees are subtle microaggressions and verbal disrespect. Workplace incivility has a negative impact on residents concerning their emotional status and job performance. Role play and mentoring by seniors,leadership qualities by setting examples, effective communication and reflection on your own action are the best coping strategies.